Human Capital in the Siberian Remote Provinces: Digital Prospects - Ibragimov, Radiy Nazibovich (KnE Social Sciences, 2021)
The aim of this study is to substantiate the need to interpret the concept of ‘human capital’ through the prism of the theory of passionarity with reference to such sociospatial loci as remote Siberian territories. Based on the fact that in these conditions humanization is the primary national task, the most personally valuable and socially significant quality that should be potentially capitalized is vital business drive. At this stage of the study, the identification of carriers of the attribute of passionarity is carried out by the “snowball method”, and a meaningful analysis of their life programs is carried out by the method of formalized interviews. The study revealed that the specifics of the formation of human capital in sparsely populated areas of Siberia are its fundamental multidimensionality, and it is the digital equipment of this process that gives real prospects for its implementation. Keywords: Human capital, passionarity, digitalization, capitalization scenario